Evaluasi Pelaksanaan Program Sustainable Development Goals (SDGS) Desa Dalam Meningkatkan Pekerjaan Layak Dan Pertumbuhan Ekonomi Di Kabupaten Lombok Timur Tahun 2024 - Utomo, Danang Prio; Ali, Muhammad; Sholihah, Nadia Atma; Asih, Elma Bakti (Universitas Hamzanwadi, 2025)
This study aims to: 1) Determine the implementation of the Sustainable Development Goals (SDGs) program in increasing decent work and economic growth in East Lombok Regency, 2) Determine the evaluation of the Sustainable Development Goals (SDGs) program in increasing decent work and economic growth in East Lombok Regency. This study is a qualitative descriptive study, using data collection techniques such as observation, interviews, questionnaires, and documentation in three villages. 20 respondents were selected using purposive sampling techniques, using Miles and Huberman data analysis techniques. Then, the data were analyzed using an interactive model that includes data reduction, data presentation, and conclusion drawing. Based on the research results, which refer to eight indicators: socialization, knowledge, effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy of program targets. Therefore, it can be concluded that the implementation of the Village Sustainable Development Goals (SDGs) program to increase decent work and economic growth in East Lombok Regency has been carried out in accordance with applicable provisions and regulations. However, Goal 8 has not been implemented properly due to problems or shortcomings. Therefore, the evaluation of the implementation of the Sustainable Development Goals (SDGs) program is considered ineffective because most villages and communities have not yet felt the positive impact of the pre-employment card distribution program and the training provided by the vocational training centers